Tracking e-learning through published papers: a systematic review - Rodrigues, H.; Almeida, F.; Figueiredo, V.; Lopes, S. L. (Computers and Education, 2019)
Electronic learning (e-learning) is a broader approach to learning that brings new opportunities for learning and teaching in many fields of education far from the traditional classroom environment. Over the past decades, research in the field indicates a proliferation of e-learning contents and discrepancies that affect interoperability patterns in education for students and teachers; however, little has been done to assess the usability of e-learning systems. From a different perspective, this study aims to provide information on the numerous findings relating to the cumulative results of e-learning in education. This systematic review uses a full protocol with the aim of standardizing and specifying all the procedures adopted to collect and code 99 academic articles from 2010 to 2018 with keywords: education and e-learning. The text analysis as conducted using the qualitative software Leximancer to extract meaning from the large number of articles retrieved. The results highlight four dominant themes, namely education systems and learning issues that in turn promote student behaviours and the use of online learning tools. This research contributes towards providing research propositions that can be used in a cogent theoretical framework and, based on the analysis, we also propose a new definition of e-learning.